Biocompatibilidade de scaffold nanofibrosos contendo antibióticos sob parâmetros inflamatórios e de estresse oxidativo em modelo de implantação subcutânea em ratos - Moro, Juliana da Silva (2017)
Scaffold are biomaterials widely used in medical and industrial areas and can be used as potential pharmacological supports for regenerative medicine and in drug delivery systems. Therefore, the present study aims to evaluate the biocompatibility of polydioxanone nanofibrous scaffold (PDS) containing the antibiotics Metronidazole or Ciprofloxacin in an animal model of subcutaneous implantation. Sixty Wistar rats, adults and males were randomly divided into six experimental groups: (I) SHAM (negative control, without scaffold; n = 10), (II) PDS (positive control, PDS without antimicrobial; ) 1MET (one scaffold PDS 25m% Metronidazole; n=10); (IV) 2MET (two scaffold PDS 25m% Metronidazole; n = 10), (V) 1CIPRO (one scaffold PDS 25m% Ciprofloxacin; n = 10) and After 3 and 30 days of dorsal subcutaneous implantation of the scaffold, half of each experimental group was anesthetized, euthanized, and the tissue corresponding to that area was removed for the histomorphometric evaluations In addition, plasma was used for the analysis of oxidative biomarkers. Histological analysis showed that groups with PDS scaffold containing antimicrobials showed, after 3 days of implantation, mild to moderate local inflammation, with increase in number of blood vessels, showing greater intensity in the groups with two scaffold of PDS containing the antimicrobials. However, 30 days after implantation, a significant reduction (p = 0.019) of the inflammatory response was observed in all experimental groups. Three days after the implantation of the scaffold, the 2MET, 1CIPRO and 2CIPRO groups presented the highest levels of reactive species (RE) when compared to the SHAM group. Lipid peroxidation was observed in all groups that had scaffold implanted subcutaneously, with the exception of the 1CIPRO group. In addition, the presence of scaffold with Metronidazole or Ciprofloxacin in the dorsal subcutaneous region was related to increased levels of the non-enzymatic plasma antioxidant GSH and VIT C. Thirty days after the implantation of the scaffold, all groups had higher levels of ER Compared to the SHAM group, but with levels of lipid peroxidation, GSH and VIT C similar to each other. From the results of this study, we can suggest that PDS scaffold containing the antimicrobials Metronidazole or Ciprofloxacin are biocompatible, and drug delivery systems may be promising